SYNTHESIS AND CHARACTERIZATION OF CROSSLINKED POLYMER BASED ON CYCLOPENTANONE CONTAINING ZINC METAL - A.Arun,; K. Karthikeyan , (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2022)
Two novel crosslinked polymers are synthesized using the crosslinker 2,6 – bis (4- methacryloyloxy benzylidene) cyclopentanone (BMACP). The crosslinker is prepared using the reaction between the cyclopentanone based arylidine compounds with the methacryloyl chloride. The two crosslinked polymers were prepared using commercially available monomers Styrene (s) and N-vinyl-2-pyrrolidone (NVP). The crosslinking polymerization is prepared in the presence of zinc acetate to make the novel copolymer as metal incorporated copolymers. The product indeed formed. The formed BMACP and crosslinked polymers were well characterized using the available techniques like FTIR, NMR and TGA analysis. The formed crosslinked polymers can be highly useful for the organic compound synthesis as a heterogeneous catalyst